2013
DOI: 10.3906/sag-1205-85
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin-8, CA-125 levels, neutrophil to lymphocyte ratios and combined markers in the diagnosis of endometriosis

Abstract: Flash vacuum pyrolysis (FVP) or thermolysis (FVT), an environmentally friendly method for studying organic reaction mechanisms as well as synthesis, was applied to a series of oxalate dimers (1, 3, 5, 7, 9, 11, 13, and 15) to synthesise monomeric enes, dienes, and a triene (2, 4, 6, 8, 10, 12, 14, and 16). All steroidal monomers were identified by spectroscopic means.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Twenty‐two studies included 3626 participants (Figure ) . Nineteen prospective observational studies and three retrospective observational studies were included for analysis. Two studies did not include analysable data and the authors could not be contacted .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty‐two studies included 3626 participants (Figure ) . Nineteen prospective observational studies and three retrospective observational studies were included for analysis. Two studies did not include analysable data and the authors could not be contacted .…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies recruited patients from infertility clinics and eight studies included recruited patients from general gynaecology clinic or elective gynaecological theatre sessions . Twelve studies reported including patients with pain symptoms . Twelve studies recruited patients with pre‐operative imaging available indicating an ovarian cyst .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations